An Overview on the Differential Interplay Among Neurons–Astrocytes–Microglia in CA1 and CA3 Hippocampus in Hypoxia/Ischemia - Lana, Daniele; Ugolini, Filippo; Giovannini, Maria G. (Frontiers in Cellular Neuroscience, 2020)
Neurons have been long regarded as the basic functional cells of the brain, whereas astrocytes and microglia have been regarded only as elements of support. However, proper intercommunication among neurons–astrocytes–microglia is of fundamental importance for the functional organization of the brain. Perturbation in the regulation of brain energy metabolism not only in neurons but also in astrocytes and microglia may be one of the pathophysiological mechanisms of neurodegeneration, especially in hypoxia/ischemia. Glial activation has long been considered detrimental for survival of neurons, but recently it appears that glial responses to an insult are not equal but vary in different brain areas. In this review, we first take into consideration the modifications of the vascular unit of the glymphatic system and glial metabolism in hypoxic conditions. Using the method of triple-labeling fluorescent immunohistochemistry coupled with confocal microscopy (TIC), we recently studied the interplay among neurons, astrocytes, and microglia in chronic brain hypoperfusion. We evaluated the quantitative and morpho-functional alterations of the neuron–astrocyte–microglia triads comparing the hippocampal CA1 area, more vulnerable to ischemia, to the CA3 area, less vulnerable. In these contiguous and interconnected areas, in the same experimental hypoxic conditions, astrocytes and microglia show differential, finely regulated, region-specific reactivities. In both areas, astrocytes and microglia form triad clusters with apoptotic, degenerating neurons. In the neuron–astrocyte–microglia triads, the cell body of a damaged neuron is infiltrated and bisected by branches of astrocyte that create a microscar around it while a microglial cell phagocytoses the damaged neuron. These coordinated actions are consistent with the scavenging and protective activities of microglia. In hypoxia, the neuron–astrocyte–microglia triads are more numerous in CA3 than in CA1, further indicating their protective effects. These data, taken from contiguous and interconnected hippocampal areas, demonstrate that glial response to the same hypoxic insult is not equal but varies significantly. Understanding the differences of glial reactivity is of great interest to explain the differential susceptibility of hippocampal areas to hypoxia/ischemia. Further studies may evidence the differential reactivity of glia in different brain areas, explaining the higher or lower sensitivity of these areas to different insults and whether glia may represent a target for future therapeutic interventions.